Diversity and spatial distribution of non-timber forest products in the Mamasa sub-watershed, Sulawesi, Indonesia - MUHAMMAD ALRIEFQI PALGUNADI; ACHMAD FUAD FATHURRAHMAN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Palgunadi MA, Fathurrahman AF. 2026. Diversity and spatial distribution of non-timber forest products in the Mamasa sub-watershed, Sulawesi, Indonesia. Biodiversitas 27 (4): d270418. https://doi.org/10.13057/biodiv/d270418. Mamasa sub-watershed is undergoing rapid ecological degradation driven by land-use change, yet its potential for biodiversity-based livelihood strategies, especially through Non-Timber Forest Products (NTFPs), remains poorly documented. This study addresses this gap by conducting a comprehensive NTFP inventory and spatial assessment to support ecosystem-based watershed management. A stratified systematic sampling with random start design was applied using 154 cluster plots across the 104,680.52 ha sub-watershed. Species density, relative frequency, and Importance Value Index (IVI) were quantified, followed by spatial analysis of NTFP distribution patterns. Utilization categories were assigned based on established literature rather than household surveys, providing an assessment of potential functional uses instead of site-specific extraction practices. A total of 84 NTFP species were recorded. Pinus merkusii was the most dominant species (RD 16.21%; IVI 22.03), while Arenga pinnata showed the widest spatial distribution (RF 9.80%; IVI 16.16), followed by ecologically resilient understory species such as Cyathea arborea, Calamus rotang, and Diplazium esculentum. Spatial analysis based on mapped distribution indicated visually clustered patterns of high-value NTFPs across secondary forests, riparian corridors, and forest–agriculture interfaces. These findings indicate that NTFPs may function as important ecological and potentially socio-economic components of the Mamasa watershed. While no livelihood or income data were collected in this study, the documented species and their literature-based uses suggest potential pathways for ecosystem-supportive and sustainable livelihood opportunities. These results provide a spatially explicit basis for targeted NTFP zoning, enrichment planting in degraded areas, and the development of sustainable NTFP-based livelihood strategies that simultaneously strengthen ecosystem resilience and watershed management.